Pendampingan Publikasi Artikel Pengabdian Kepada Masyarakat Bagi Mahasiswa KKN Ke-82 UIN Raden Fatah Palembang - Firmansyah; Mukti Ali; Erisa Ardika Prasada; Mochammad Rian Ahdian Morena (Pusmedia Group Indonesia, 2026)
This community service activity aimed to enhance the understanding and skills of students participating in the 82nd Community Service Program (KKN) at UIN Raden Fatah Palembang in writing and publishing scientific articles based on community service activities. The activity was conducted over 22 days and involved 30 students from various academic programs. The activity employed a service-learning approach, comprising the stages of planning, implementation, evaluation, and reporting. The results of the activity showed a significant improvement in the participants’ abilities, marked by an increase in the average score from 50.6 on the pre-test to 76.4 on the post-test. Improvements occurred across all aspects, particularly in understanding article structure and the ability to organize discussions. Additionally, participants were able to produce more systematic article drafts that adhered to scientific writing guidelines. This activity also fostered greater student awareness of the importance of scientific publication as an outcome of community service activities. The activity had limitations, including the relatively short duration of the mentoring, the heterogeneity of participants’ abilities, and limited access to scientific reference sources. Therefore, it is recommended that universities develop more sustainable mentoring programs, that faculty members provide guidance through the publication stage, and that students independently improve their academic literacy. Institutional support is also needed to provide access to references and a publication monitoring system to ensure the sustainability of the program’s outcomes. This finding theoretically reinforces the concept of reflective learning. In practice, this activity improves the quality of Community Service Program (KKN) outcomes, particularly scientific publications, and can serve as a model for mentoring in community service at universities.